1980
DOI: 10.1136/bmj.280.6218.894
|View full text |Cite
|
Sign up to set email alerts
|

Sleep apnoea in acromegaly.

Abstract: consultant physician W VAN'T HOFF, Ma, FRcp, consultant physician important in acromegaly, and it may be central, obstructive, or mixed. Polygraphic nocturnal monitoring is indicated to assess these patients properly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(39 citation statements)
references
References 7 publications
1
37
0
1
Order By: Relevance
“…Many studies showed higher frequency of SAS in active acromegalic patients with a positive correlation with GH/IGF1 levels (3,12,13). Conversely, in the study of Grunstein et al (1) only the presence of central apnoea (CA), but not the degree of sleep apnoea, was associated with the disease activity.…”
Section: Introductionmentioning
confidence: 80%
“…Many studies showed higher frequency of SAS in active acromegalic patients with a positive correlation with GH/IGF1 levels (3,12,13). Conversely, in the study of Grunstein et al (1) only the presence of central apnoea (CA), but not the degree of sleep apnoea, was associated with the disease activity.…”
Section: Introductionmentioning
confidence: 80%
“…AHI) with cardiorespiratory monitoring and various parameters in Japanese acromegalic patients, which to our knowledge is the first such report. Previous studies in European acromegalic patients showed that SDB correlates with high levels of GH and IGF-1 [3,13,15], aging [10,12,14,15], male gender, BMI [14], WC [14], neck circumference [15] and tongue size [30,31]. Although we reported previously that AHI correlated with BMI and WC in diabetic patients [20,21], the present study found no correlation between AHI and BMI and WC in acromegalic patients (Table 2), probably because acromegaly is often a disease with little fat but organ hypertrophy, different from diabetes.…”
Section: Correlation Analysis Between Ahi and Measured Parametersmentioning
confidence: 99%
“…Infiltration of upper airway muscles and soft tissues can impair muscle function and reduce the upper airway lumen, as in myxoedema [47], acromegaly [48,49], involvement by neoplastic processes [50], and mucopolysaccharidoses [51], all of which have been associated with a predisposition to OSA. Treatment of the underlying process can reverse upper airway obstruction [47,50].…”
Section: Reduced Upper Airway Calibrementioning
confidence: 99%